Hubungan Paritas dengan Kejadian Ketuban Pecah Dini - Desi pramita sari desi Pramita sari (Jurnal Medika : Karya Ilmiah Kesehatan, 2021)
Premature rupture of membranes can cause various complications such as infection, prolonged parturition, postpartum hemorrhage, maternal morbidity and mortality, while in the fetus PROM can cause premature birth, decreased umbilical cord, hypoxia and secondary asphyxia. Based on the data taken at Batam city, the highest number of PROM cases from 3 hospitals was 546 cases, Harapan Bunda’s Hospital. This study aims to determine relationship Parity with premature rupture of membranes at Harapan Bunda Hospital Batam City. This research used method quantitative analitic survey with cross sectional design with 60 samples. The Conclusion the results obtained were there is relationship parity with premature rupture of membranes (p value = 0,001). Suggestions to clients and community to increase their knowledge about the cause PROM so that they can prevent or detect early complications that will occur in the future.